2015
DOI: 10.1007/s00280-015-2693-z
|View full text |Cite
|
Sign up to set email alerts
|

Parallel phase Ib studies of two schedules of buparlisib (BKM120) plus carboplatin and paclitaxel (q21 days or q28 days) for patients with advanced solid tumors

Abstract: The addition of buparlisib to carboplatin + paclitaxel was well tolerated, and preliminary activity was notable against tumors with loss of PTEN expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…This latter statement is supported by the increased cytotoxicity observed in tumor cells of different origins to chemotherapy agents such as microtubule-targeting drugs (paclitaxel, docetaxel and vinblastine) [115], topotecan [116], cisplatin [117], and doxorubicin [118], when treatment was combined with inhibitors of components of PI3K/Akt pathway. Likewise, early evidence of antitumor activity, induced by either inhibiting Akt using MK-2206 [119] plus carboplatin and paclitaxel, docetaxel, or erlotinib, or inhibiting PI3K using the pan-class 1A PI3K inhibitor BKM120 [120] plus carboplatin and paclitaxel in patients with different solid tumors, supports the above-described role for PI3K/Akt in resistance to chemotherapy agents [119,120].…”
Section: Importance Of Akt In Radiotherapy Resistancementioning
confidence: 71%
“…This latter statement is supported by the increased cytotoxicity observed in tumor cells of different origins to chemotherapy agents such as microtubule-targeting drugs (paclitaxel, docetaxel and vinblastine) [115], topotecan [116], cisplatin [117], and doxorubicin [118], when treatment was combined with inhibitors of components of PI3K/Akt pathway. Likewise, early evidence of antitumor activity, induced by either inhibiting Akt using MK-2206 [119] plus carboplatin and paclitaxel, docetaxel, or erlotinib, or inhibiting PI3K using the pan-class 1A PI3K inhibitor BKM120 [120] plus carboplatin and paclitaxel in patients with different solid tumors, supports the above-described role for PI3K/Akt in resistance to chemotherapy agents [119,120].…”
Section: Importance Of Akt In Radiotherapy Resistancementioning
confidence: 71%
“…Two studies have evaluated BKM120 with paclitaxel or paclitaxel/carboplatin [11, 13]. In both studies, the MTD of BKM120 was the same as the single-agent MTD (100 mg daily) and the combination was reported to be well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…Dose limiting toxicity (DLT) included hyperglycemia, skin rash, epigastric pain, and mood disorders. Two subsequent studies have confirmed that BKM120 is well tolerated when combined with both the aromatase inhibitor letrozole in estrogen receptor-positive metastatic breast cancer and carboplatin plus paclitaxel in advanced solid tumors [11, 12]. Based on the above rationale, we conducted a phase I trial of BKM120 in combination with mFOLFOX6 in order to determine the MTD of the combination in patients with refractory advanced solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…We established the MTD/recommended phase II dose (RP2D) for the combination and reported that the addition of buparlisib to q3 weeks carboplatin (AUC 5) and paclitaxel (175 mg/m2) was well tolerated and permitted full dosing of buparlisib (100 mg/daily) compared with the alternate q4 weeks carboplatin (AUC 5) and paclitaxel schedule of 80 mg/m2 (days 1, 8, and 15) that limited buparlisib escalation to 80mg/day. [18] Additive clinically significant myelosuppressive effects were not seen with the q3 weeks combination. In view of the favorable safety profile seen with the combination in the q3 week schedule, we sought to explore a higher dose of this regimen in an expansion cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, we also observed in the dose escalation study, promising activity against tumors with loss of PTEN expression. [18] An observation with some mechanistic rationale, given PTEN deficient tumors are dependent on p110β PI3K signaling and buparlisib having activity against this isoform, is potentially desirable for these tumors. [19,20] Indeed pre-clinical studies have shown synergistic lethality with the combination of buparlisib and platinum-based chemotherapy in PTEN deficient xenografts.…”
Section: Introductionmentioning
confidence: 99%